Analisis Kinerja Ruas Jalan Akibat Putar Balik Pada KM 23 Depan Grand Mall Sampai Dengan Simpang Tiga Pasar Batangase Kabupaten Maros - Musdalifah, Musdalifah B; Nurdin, Abd. Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
This study aims to determine the performance of roads along the Makassar Maros axis road at KM 23 in front of the Grand Mall to the Batangase market junction due to a u-turn from the results of calculating the large volume of traffic, capacity and level of road service. The focus of this research is located on Jalan Poros Makassar Maros KM 23 starting from the front round of Graha Cemerlang Housing to the front round of Zazil Bakery. The data needed is primary data consisting of geometric road sections, vehicle volume, and vehicle speed and secondary data, namely the 1997 Road Transportation Guidebook and the Indonesian Road Capacity Manual (MKJI). The results of the analysis are obtained from the calculations at point 1 and point 2 level road services are included in service level D, so the performance of roads along the Makassar - Maros Axis KM 23 (Front of the Grand Mall to the Batangase market junction) due to U-turns is low speed and varies with delays from both the same direction and the opposite opposite direction or traffic conditions are starting to become unstable.